2008
DOI: 10.1002/lsm.20655
|View full text |Cite
|
Sign up to set email alerts
|

Topical delivery of methotrexate via skin pretreated with physical enhancement techniques: low‐fluence erbium:YAG laser and electroporation

Abstract: The results shown in the present study encourage further investigation of laser- and electroporation-assisted topical drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 38 publications
1
28
0
3
Order By: Relevance
“…delivery of MTX has previously been investigated by chemical enhancement strategies and physical barrier disruption techniques such as iontophoresis, microneedles, diode laser, fullablative Erbium Yttrium Aluminum Garnet (Er:YAG) laser, and intracutaneous injections [2][3][4][5][6][7][8]. In vitro studies of these techniques have shown that MTX can be delivered topically [3][4][5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…delivery of MTX has previously been investigated by chemical enhancement strategies and physical barrier disruption techniques such as iontophoresis, microneedles, diode laser, fullablative Erbium Yttrium Aluminum Garnet (Er:YAG) laser, and intracutaneous injections [2][3][4][5][6][7][8]. In vitro studies of these techniques have shown that MTX can be delivered topically [3][4][5].…”
mentioning
confidence: 99%
“…In vitro studies of these techniques have shown that MTX can be delivered topically [3][4][5]. However, the efficacy of topical MTX in in vivo studies on animals and human psoriasis patients has shown conflicting results, which may be explained by imprecise drug delivery [6][7][8][9][10].…”
mentioning
confidence: 99%
“…72 More recent work using infrared (IR) or visible wavelength lasers has shown increased permeability to a range of small lipophilic and hydrophilic compounds. 55,56,[73][74][75][76] Control of the degree of ablation can be achieved by setting the laser parameters, including wavelength and pulse energy, frequency, and width. For example, a recent study by Gomez et al 74 used a Q -switched Nd:YAG laser, emitting radiation at 1064, 532 (second harmonic), and 355 nm (third harmonic) to treat excised rabbit ear skin before 5 -FU permeation.…”
Section: Lasersmentioning
confidence: 99%
“…The enhancing effect was more pronounced after applying the laser. Electroporation treatment resulted in a twofold increase in MTX flux, laser pretreatment produced a 3-to 80-fold enhancement and combination of laser and electroporation pretreatment resulted in a higher drug permeation than either technique alone [80] .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Therefore attempts have been made to increase transdermal transport through electroporation [79,80] and using an erbium:YAG laser in animal models. Both techniques significantly enhanced the permeation of MTX.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%